Chinua Achebe: The Novelist as Critic and Editor - SHEHU, Halima; CHIKE-OKOLI, F.C. (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Chinua Achebe is widely acknowledged as a foundational figure in the development of modern African literature, particularly for his novels that explore the complexities of both pre-colonial and post-colonial African experiences. However, in addition to his fiction, Achebe’s contributions as a critic and editor have profoundly influenced literary criticism and shaped global understanding of African literature. His efforts to amplify African voices through his critical essays, his role as the founding editor of the Heinemann African Writers Series, and his editorship of the literary journal Okike have been pivotal in asserting the significance of African perspectives thereby highlighting his multifaceted impact on the literary world. While scholarly studies focus predominantly on his fiction, Achebe's critical essays and editorial work merit further scholarly attention due to their lasting influence on world literature. Employing postcolonial theory as theoretical framework and methodology, this paper integrates textual analysis, critical discourse analysis, and paratextual examination to investigate Achebe’s essays in Morning Yet on Creation Day and Hopes and Impediments, as well as his editorial interventions. Through this methodological approach, the study explores how Achebe’s work addresses the challenges encountered by African writers, interrogates the role of literature in postcolonial societies, and elucidates the potential of literature to foster cultural reclamation and social transformation.